Development of Omni-directional robotic car with human tracking mechanism - A. Rahman, M. Safwan; Htike@Muhammad Yusof, Zaw Zaw (2016)
Omni-directional robotic car is a special type of mobile robot. It has the ability to move sideways without changing its headings. It is superior in term of mobility and agility as compared to the typical conventional steering and differential drive mobile robot due to its holonomic capability which is particularly useful in a narrow space. The proposed system will address the mobility limitation of the conventional mobile robot. This report presents the design and development of an omni-directional holonomic robotic car with the capability of obstacle avoidance as well as human tracking. First, literature review was performed to see the different type of wheel configuration as well as its working principle. From the understanding, the specification and the design of the robot were determined. Some mathematical analyses as well as software simulation has been carried out to evaluate the performance. Using the information obtained from the analysis, hardware selection for the system was conducted and the system was then built. Experimental testing indicates that the system performed as expected which was similar to the result of the software simulation. Several performance evaluation were performed. For mobility, orientation and speed of the robot played a crucial role in determining the tendency of the robot to tumble and overcoming bump. Optimization relationship of both tendencies were also discussed. Human tracking performance fared poorly due to the subpar camera used. Overall, the performance of the system was satisfactory.